Pengembangan Lembar Kerja Mahasiswa (LKM) Berbasis Penemuan Terbimbing Pada Materi Hasil Kali Vektor - Noviana Agus, Ria; Sholahudin , Usep (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2024)
The aim of this research is based on students' needs for teaching materials in vector analysis courses. This research develops teaching materials in the form of student worksheets (LKM) based on guided discovery in vector product material. Development model using 4D. The research subjects were 11 UNSERA Mathematics Education study program students. Research instruments include questionnaires, observation sheets and interviews. The conclusion from the research results is that LKM based on guided discovery is valid, practical and effective. This LKM teaching material can be a support in vector analysis lectures on vector multiplication material.